The holy and the hybrid : navigating the Church's digital reformation - Panzer, Ryan M. (Minneapolis : Fortress Press, 2022)
The digital reformation accelerated Friday, March 13, 2020, when the President declared a national emergency due to the Covid-19 pandemic. Church leaders quickly cobbled together virtual worship services, assuming faith communities would be apart for only a few weeks. As weeks stretched into months, however, leaders began to acknowledge that there was no going back to a previous normal, to a time of mostly in-person faith communities.In The Holy and the Hybrid: Navigating the Church's Digital Reformation, Ryan M. Panzer helps church leaders develop hybrid ministries through aligning the shared mission of the church with the collective values of our tech-shaped culture. The goal of the book is to help build communities that serve as the hands and feet of Christ simultaneously online and offline.Church will be at its best, Panzer argues, when we begin our conversations on technology not with apps or IT infrastructure but with values. The more we embrace the value of collaboration in particular, the more missional our faith communities will become and the more effectively we will equip communities for faithful service.'We take up this work,'says Panzer,'not for the sake of relevance or trendiness but for the sake of the gospel, not to promote institutional vitality but to form disciples.'With his guidance, church leaders will feel confident coaching their communities through this time of great change.
The last coffee hour: analog church, disrupted -- The first YouTube baptism: the digital-only church -- The next Easter: emerging hybrid church community -- The first day back: sustaining hybrid ministry -- Campfire worship: the limits and opportunities of hybrid church.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on August 10, 2022).
JSTOR
Keywords: Public worship; Technology -- Religious aspects -- Christianity; Culte public; Christian Church; RELIGION; Christian Ministry; Public worship; Technology -- Religious aspects -- Christianity